Exploring the therapeutic potential of tDCS, TMS and DBS in overcoming tobacco use disorder: an umbrella review - Graziella Orrù; Marina Baroni; Ciro Conversano; Angelo Gemignani (AIMS Neuroscience)
The purpose of the present study was to investigate the effects of neuromodulation techniques, including transcranial direct current stimulation, transcranial magnetic stimulation, and deep brain stimulation, on the treatments of nicotine dependence. Specifically, our objective was to assess the existing evidence by conducting an umbrella review of systematic reviews. The quality of the included studies was evaluated using the standardized tools designed to evaluate systematic reviews. The PubMed/MEDLINE database was queried for systematic reviews, and yielded 7 systematic reviews with a substantial sample size (N = 4,252), some of which included meta-analyses. A significant finding across these studies was the effectiveness of neuromodulation techniques to reduce nicotine cravings and consumption, through the evidence remains not yet conclusive. A significant efficacy of transcranial direct current stimulation and repetitive transcranial magnetic stimulation that targeted the dorsolateral prefrontal cortex was found, as well as the lateral prefrontal cortex and insula bilaterally, on smoking frequency and craving. Moreover, smoking behaviors may also be positively affected by the use of deep brain stimulation (DBS) targeting the nucleus accumbens. In conclusion, neuromodulation approaches hold promise as effective treatments for tobacco use disorder. Nonetheless, further research is required to comprehensively understand their effectiveness and to determine if combining them with other treatments can aid individuals to successfully quit smoking.